Looking Beyond Assumptions to Understand Relationship Dynamics in Bullying - Mishna, Faye; Birze, Arija; Greenblatt, Andrea; Pepler, Debra (Frontiers in Psychology, 2021)
To account for the complex relationships and processes that constitute the phenomenon of bullying, it is critical to understand how students and their parents and teachers conceptualize traditional and cyberbullying. Qualitative data were drawn from a mixed-methods longitudinal study on cyberbullying. Semi-structured interviews were held with Canadian students in grades 4, 7, and 10 in a large urban school board, and their parents and teachers. To account for the complexity and interactions of different systems of relationships, the purpose of the current article is to examine how students and their matched parents and teachers understand traditional and cyberbullying. Central to participants’ understanding of traditional and cyberbullying was whether they considered bullying to represent harmful relationship dynamics. Three main assumptions emerged as shaping participants’ understanding of bullying and appeared to obscure the deep relationship processes in bullying: a) assumptions of gender in bullying, b) type of bullying—comparing traditional and cyberbullying, and c) physical bullying as disconnected from relationship dynamics. It is essential that assessment, education, and prevention and intervention strategies in traditional and cyberbullying be informed by the inherent relationships in bullying and be implemented at multiple levels of relationships and broader social systems.